(untitled) (KULT_online, 2022)
In his contribution to media and intellectual history in the West-German New Left, Moritz Neuffer gives insight into the role of journalistic forms in the reception and production of theory with the example of the magazine alternative. In particular, his work profits from its continuous effort to keep the societal context and the role of actors in view.